Proximate Composition of Some Selected Seaweeds from Coastal Areas of Cox’s Bazar and the St. Martin’s Island, Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The present study assesses the proximate composition of eight wild seaweed species viz. Hypnea sp., Enteromorpha sp., Sargassum sp., Hydroclathrus clathratus, Padina pavonica, Colpomenia sinuosa, Petalonia fascia and Dictyota ciliolata and one cultured species viz. Hypnea sp. collected from western coast of the St. Martin’s Island and Nunairchhara, Cox’s Bazar, respectively. Standard analytical methods were used to estimate moisture, ash, lipid, crude fiber and protein contents, while carbohydrates were measured by subtracting ash, fat, fiber and protein contents from 100 on a dry weight basis. Results showed average moisture content in different seaweed species ranged between 12.09% to 29.65% and varied from species to species. Maximum ash content was found in brown seaweed H. clathratus (61.98%), while the lowest was recorded in wild red algae Hypnea sp. (7.05%). This study showed mean lipid contents in all seaweed species were much lower than other contents of proximate composition. The highest crude fiber content was observed in P. fascia (10.08±0.07%), while the lowest was observed in Enteromorpha sp. (0.23±0.01%). The highest protein (23.64±1.44%) and carbohydrate content (46.71±0.54%) was found in Hypnea sp. This study showed that mean carbohydrate content was higher in Rhodophyta, Chlorophyta and Phaeophyta, whereas, lipid content was lower in the three groups. Proximate composition of ash, lipid, crude fiber and protein content within species varied due to habitat differences, changes of body structures or physiological alterations, changes in growth rates and photosynthetic function of seaweed species and geographical differences. The mean moisture and ash content were the highest in cultured Hypnea sp., whereas, lipid, crude fiber, protein and carbohydrate were formed to the highest in wild Hypnea sp. Results suggest wild Hypnea sp. was much nutritive because of having higher amount of protein, fiber, carbohydrate and lipid than cultured ones. The study indicates that seaweeds might be used as a potential source of protein, fiber and carbohydrate.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 113-122